2016
DOI: 10.3233/npm-16915084
|View full text |Cite
|
Sign up to set email alerts
|

PIVKA-II correlates with INR but not protein C or protein S concentrations in cord blood among newborns

Abstract: PIVKA-II seems to be a sensitive indicator of mild VK deficiency. Further studies are needed to investigate the lack of relationship between PIVKA-II and functional protein C or S levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Another recent study showed that, in subclinical VK deficiency, PIVKA-II did not correlate with functional protein C levels (20). One possible explanation is that protein C has a more sensitive response to changes in the hepatic VK-dependent carboxylase system (21,22).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Another recent study showed that, in subclinical VK deficiency, PIVKA-II did not correlate with functional protein C levels (20). One possible explanation is that protein C has a more sensitive response to changes in the hepatic VK-dependent carboxylase system (21,22).…”
Section: Discussionmentioning
confidence: 97%
“…Cholestatic newborns are at risk for acquired coagulopathy due to reduced VK absorption (20) and limited tissue reserves that are rapidly catabolized, with 60-70% of a single VK dose being excreted in about 3 days (4). Indeed, oral or parenteral VK supplementation is suggested in full enterally-fed preterm newborns with IFALD, although effective VK intestinal absorption in these patients is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the correlation between Na-DHA dose and serum levels of Vk1 may be a reasonable explanation. How Na-DHA affects the activity/expression of VKOR, VKORC12425 and protein induced by Vitamin k absence/antagonist II (PIVKA II)26 in females and males will be studied carefully in our next work.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] Interestingly, there is a significant linear correlation between INR and PIVKA-II, suggesting that PIVKA-II levels can serve as an alternative to PT/INR in assessing the VK deficient status in neonates. 26 In addition, elevated PIVKA-II precedes any subsequent change in PT. Elevated PIVKA-II levels can be detected before any changes in PT become apparent.…”
Section: Introductionmentioning
confidence: 99%
“…PIVKA‐II levels can be measured by detecting antibodies specific to undercarboxylated prothrombin 23–25 . Interestingly, there is a significant linear correlation between INR and PIVKA‐II, suggesting that PIVKA‐II levels can serve as an alternative to PT/INR in assessing the VK deficient status in neonates 26 . In addition, elevated PIVKA‐II precedes any subsequent change in PT.…”
Section: Introductionmentioning
confidence: 99%